The road from success to underperformance and the return to sustainable high-level performance. A case study of an elite cross-country skier - Moxnes, E. F. (Norwegian University of Science and Technology, 2022)
Purpose: The primary purposes of this case study are threefold: 1) to describe the training of Didrik Tønseth (DT) leading to world class performance in cross-country skiing; 2) to determine possible factors associated with unexpected underperformance, ending in a non-functioning state, and 3) prospectively describe the participants multidisciplinary approach when returning to sustainable high-level performance.